The Cultur of School Environment Associated with Overweight in Urban Adolescent - Oktia Woro Kasmini Handayani (Intelektual Pustaka Media Utama, 2013)
The number of cases in overweight adolescents tend to increase will have an impact on the quality of Human Resources (HR) in the present and future. For that, the problem in this research is what the cultural of school environment factors related to the overwight in urban adolescent.This study was a cross sectional survey. The population in this study is all high school students Kesatrian 2 Semarang in 2012, amounting to 918 people. Samples were 30 students selected by purposive sampling. The independent variable was the frequency of street food consumption, physical activity and the amount of pocket money. Dependent variable is overweight events. The data analysis is using chi square test.There is a relationship between the frequency of street food consumption (p= 0.020), physical activity (p= 0.030) with the risk of incidence of overweight in urban adolescents. There is no relationship between the amount of pocket money (p= 0.225) and the incidence of overweight in urban adolescent. Suggestion: 1) Urban adolescent need to understand the incidence of overweight and the factors that influence it in order to take steps to prevent overweight independently 2) For the department of health, public health center and the school need to promote prevention programs in adolescent nutrition for adolescent to have normal nutritional status.DOI: http://dx.doi.org/10.11591/ijphs.v2i3.2893